The stone home : a novel - Kim, Crystal Hana, 1987- (William Morrow, an imprint of HarperCollins Publishers, 2024)
"A hauntingly poetic family drama and coming-of-age story that reveals a dark corner of South Korean history through the eyes of a small community living in a reformatory center--a stunning work of great emotional power from the critically acclaimed author of If You Leave Me"--